In vitro myelin formation using embryonic stem cells - Kerman, Bilal Ersen; Kim, Hyung-joon; Padmanabhan, Krishnan; Mei, Arianna; Georges, Shereen; Joens, Matthew; Fitzpatrick, James; Jappelli, Roberto; Chandross, Karen; August, Paul; Gage, Fred (Company of Biologists, 2015)
Myelination in the central nervous system is the process by which oligodendrocytes form myelin sheaths around the axons of neurons. Myelination enables neurons to transmit information more quickly and more efficiently and allows for more complex brain functions; yet, remarkably, the underlying mechanism by which myelination occurs is still not fully understood. A reliable in vitro assay is essential to dissect oligodendrocyte and myelin biology. Hence, we developed a protocol to generate myelinating oligodendrocytes from mouse embryonic stem cells and established a myelin formation assay with embryonic stem cell-derived neurons in microfluidic devices. Myelin formation was quantified using a custom semi-automated method that is suitable for larger scale analysis. Finally, early myelination was followed in real time over several days and the results have led us to propose a new model for myelin formation.
Keywords: Automated Quantification; Embryonic Stem Cells; Live Imaging; Myelin; Oligodendrocyte